Kompetensi Manajerial Kepala Sekolah Dalam Pengelolaan Tenaga Pendidik di UPT SPF SD Inpres Bertingkat Labuang Baji - Sry Rahayu Febriyanti; Wahira Wahira; Muhammad Ardiansyah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study examines the principal’s managerial competence in managing teaching staff at UPT SPF SD Inpres Bertingkat Labuang Baji. It employs a descriptive qualitative approach, with data sourced from the school principal and teaching staff. Data were collected through interviews, documentation, and observation, and were then analyzed using data collection, data reduction, data display, and drawing final conclusions. Data validity was ensured through triangulation techniques. The results of the study indicate that teacher planning at UPT SPF SD Inpres Bertingkat Labuang Baji has been carried out systematically and in an organized manner, taking into account the number of students and classes to determine teacher requirements. The analysis shows that the number of available teachers, which is 14, is in accordance with the number of study groups and students. Teacher recruitment is conducted through the P3K and Laskar Pelangi programs, with a minimum educational requirement of a bachelor’s degree (S1), and nearly 90% of the teachers are certified. The selection process is rigorous, including interviews conducted by the principal to ensure academic qualifications and alignment with the school’s needs. The development and training of teaching staff at the school are focused on mastering educational technology, which has become increasingly important due to advancements in the field. However, the principal has not yet organized specific workshops to enhance teachers’ competencies in educational technology. Instead, teachers are encouraged to learn independently through online platforms such as YouTube and Facebook. Other development programs, such as workshops, Teacher Working Groups (KKG), training on the Implementation of the Independent Curriculum, and performance management through the Merdeka Mengajar platform, have been implemented as efforts to maintain and improve teaching quality. Nevertheless, more structured training in educational technology is still greatly needed to ensure teachers’ professional competence in keeping up with current demands